1985
DOI: 10.3133/ofr85723
|View full text |Cite
|
Sign up to set email alerts
|

Reconnaissance geology of the Uqlat as Suqur Quadrangle, sheet 25/42 A, Kingdom of Saudi Arabia

Abstract: The geology of the Uqlat as Suqur quadrangle provides a detailed record of the late Proterozoic layered and intrusive rock units,-their interrelationships, and the structural evolution of a large portion of the northeastern Shield of Saudi Arabia. Four major unconformities and three well-defined intrusive episodes identified in the quadrangle provide a rational basis for describing and defining lithostratigraphic units, and for interpreting the deformational history within the region. The oldest rocks consist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

1985
1985
1988
1988

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…Exposures of marble were correlated with the Faridah marble known from the central part of the basin (Delfour, 1977;Greene, 1983). Later mapping by Johnson and Williams (1984), Pallister, (1984), and Cole (1985, suggested that the Hibshi formation may not be part of the Murdama group and is possibly younger; the name Maraghan formation was proposed to replace the name Hadiyah formation.…”
Section: Previous Studiesmentioning
confidence: 98%
See 4 more Smart Citations
“…Exposures of marble were correlated with the Faridah marble known from the central part of the basin (Delfour, 1977;Greene, 1983). Later mapping by Johnson and Williams (1984), Pallister, (1984), and Cole (1985, suggested that the Hibshi formation may not be part of the Murdama group and is possibly younger; the name Maraghan formation was proposed to replace the name Hadiyah formation.…”
Section: Previous Studiesmentioning
confidence: 98%
“…Williams (1983) showed the distribution of rocks of the Murdama group in the Samirah quadrangle, sheet 26/42C, (scale 1:100,000), which encompasses the northern part of the study area of this report. The Uglat as Suqur quadrangle, sheet 25/42A (scale 1:100,000) mapped by Cole (1985) shows the distribution of conglomerate, and overlying carbonate and coarse-grained sandstone in the southern part of the study area. Quick and DoebrichCjj/l*} and Williams and Simonds, (1985) showed the distribution of the upper Murdama group in the southeastern part of the Wadi Ash Shi'bah quadrangle, sheet 26E, (scale 1:250,000), which encompasses the western part of this study area.…”
Section: Previous Studiesmentioning
confidence: 99%
See 3 more Smart Citations